A computational study of spin glasses and its spin coupling interactions - Wong, Yi Ren (2018)
Spin Glasses are one of Physics’ most rich and complicated problems. It is a complex system with nontrivial low temperature behaviour, as a consequence of its random spin coupling interactions. The Spin Glass (SG) phase is characterized by the freezing of magnetic spins in random orientations below the critical temperature and can be observed across different SG models. These models may be diﬀerentiated from one another by the critical temperature and critical exponents measured or calculated from experiments and simulations which give rise to diﬀerent universality classes in diﬀerent regimes. We will explore in this thesis the critical phenomena of two separate new SG models − The Spin Glass Cellular Automata (SGCA) model and the Heterogeneous Spin Glass (HSG) model while reviewing other known SG models studied in literature.